Kualitas Produk, Penentuan Harga Berpengaruh terhadap Keputusan Pembelian : UD Daryono Plastik Surakarta - Rizki Darmawan Prasetya; Indra Hastuti; Khabib Alia Akhmad (Transformasi: Journal of Economics and Business Management, 2024)
The purpose of this study is to determine the effect of product quality on purchasing decisions partially, to determine the effect of pricing on purchasing decisions, and to determine the effect of product quality, and pricing on purchasing decisions case study at UD Daryono Plastik Surakarta simultaneously. A sample of 50 respondents using a sampling technique using random sampling. This study uses a quantitative method with SPSS 25 64 bit data analysis tools. The data analysis technique in this study uses validity tests, reliability tests, classical assumption tests, T tests, and F tests. The results of this study indicate that there is a positive and significant effect of product quality on purchasing decisions, there is a positive and significant effect of pricing on purchasing decisions. Then the results of the study concluded that simultaneously there is a positive and significant effect of product quality, and pricing on purchasing decisions.